Comments on "Pragmatic Socioeconomics: A Way Towards New Findings on Sources of (Housing) Market Instability". Issue 2 (15th March 2022) - Oikarinen, Elias
ABSTRACT: The article aims to create a more solid interdisciplinary bridge between sociology and mainstream economics in the study of economic behaviour, especially in terms of the housing market. This is an important aim: It would indeed be valuable to combine insights from both disciplines to find mutually benefiting synergies. The aim also is challenging, and I find the merit of this article to be in raising such discussion and providing an attempt to offer insights from sociological housing research on the understanding of housing price dynamics and thus on housing economics. Unfortunately, there are several notable complications is the article's discussion and analysis, due to which I do not think the aim of the article is reached. In any matter, I encourage the authors as well as other sociologists and housing economists to continue this debate.